Knowledge and perception of extension workers on sustainable agricultural practices - Tiraieyari, Neda; Hamzah, Azimi; Abu Samah, Bahaman; Uli, Jegak (Science Publications, 2013)
Due to the expansion of crop productions there has been an increase in the fertilizers’ use by farmers in Malaysia. Recently Sustainable Agricultural Practices (SAP) is gaining attention within agricultural sector. The Department of Agriculture facilitates regular delivery of SAP knowledge to farmers through extension workers. However extension workers’ perceptions and knowledge on SAP is not known well in Malaysia. A survey of extension workers was conducted in peninsular Malaysia to identify their perceptions and knowledge about SAP and determine the extent to which extension workers communicate SAP to the farmers. A descriptive research design was used to collect data from 400 extension workers. Results suggest extension workers’ perceptions and knowledge of SAP are favorable. Extension workers indicated that they communicate SAP information to the farmers. Further investigation from farmers’ perspectives is required to discover to what extent extension plays significant role in promoting adoption of the program.